A and B and the Question of True Nobility in Henry Medwall's Fulgens and Lucres. Issue 3 (2nd April 2016) - Peterson, Noah
ABSTRACT: Henry Medwall's Fulgens and Lucres dramatises the debate concerning the nature of true nobility found in Buonaccorso de Montemagno's Latin De Vera Nobilitate, which Medwall encountered through John Tiptoft's English translation published by Caxton in 1481. Medwall shifts the attention of his play to the legal and political concerns of the early Tudor court. The play is filled with references to contemporary court figures as well as legal concerns of the court in which Medwall served as a clerk. Medwall adds two characters simply labeled "A" and "B", and the question which is left unanswered in Montemagno and Tiptoft's texts is finally decided upon, not by the Roman senate but by Lucres. Immediately after her decision, A and B critique it. I argue that A and B do not succeed in subverting Lucres' judgment, but rather reinforce it for Medwall's audience. The two serve to illustrate what the "new-men" of Henry VII's court viewed as problematic with the older court culture.